1991
DOI: 10.1128/mcb.11.8.3860
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Xenopus cyclins B1 and B2 is not required for cell cycle transitions.

Abstract: The cdc2 kinase and B-type cyclins are known to be components of maturation-or M-phase-promoting factor (MPF). Phosphorylation of cyclin B has been reported previously and may regulate entry into and exit from mitosis and meiosis. To investigate the role of cyclin B phosphorylation, we replaced putative cdc2 kinase phosphorylation sites in Xenopus cyclins B1 and B2 by using oligonucleotide site-directed mutagenesis. We found that Ser-90 of cyclin B2 and Ser-94 or Ser-96 of cyclin B1 are the main phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
69
0
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 41 publications
(60 reference statements)
5
69
0
1
Order By: Relevance
“…One preparation was termed EGF receptor threonine 669 kinase; it now appears to be identical to human p44/ERK1 Our studies provide direct evidence in support of the same conclusion. The sequence around serine 243, P-L-S-P, satisfies an emerging consensus for p42 and p44 MAP kinase phosphorylation sites, P-X-S/T-P (Erickson et al, 1990;Alvarez et al, 1991;Gonzalez et al, 1991;Izumi and Maller, 1991;Takishima et al, 1991;Mukhopadhyay et al, 1992). Other nonpolar residues may be able to substitute for the upstream proline (Haycock et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…One preparation was termed EGF receptor threonine 669 kinase; it now appears to be identical to human p44/ERK1 Our studies provide direct evidence in support of the same conclusion. The sequence around serine 243, P-L-S-P, satisfies an emerging consensus for p42 and p44 MAP kinase phosphorylation sites, P-X-S/T-P (Erickson et al, 1990;Alvarez et al, 1991;Gonzalez et al, 1991;Izumi and Maller, 1991;Takishima et al, 1991;Mukhopadhyay et al, 1992). Other nonpolar residues may be able to substitute for the upstream proline (Haycock et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Xenopus oocyte cyclin B1 has been shown to undergo phosphorylation in vitro with MAPK or Cdc2/cyclin B on five sites, identified as Ser 2, Ser 94, Ser 96, Ser 101 and Ser 113 (Izumi and Maller, 1991;Li et al, 1995). The importance of phosphorylation at these sites in Xenopus cyclin B1 has not been established.…”
Section: Phosphorylation Of Cyclin Bmentioning
confidence: 99%
“…Entry into mitosis depends on phosphorylation of the dualspecificity phosphatase Cdc25C, which dephosphorylates Cdc2 on Tyr15 and Thr14, and hence, activates the Cdc2/cyclin B complex that catalyses the G 2 /M transition (Dunphy and Kumagai, 1991;Izumi and Maller, 1991). Although Cdc2/cyclin B itself is able to phosphorylate Cdc25C at the activating sites, forming a positive feedback loop (Izumi and Maller, 1993), the initial phosphorylation of Cdc25C occurs before Cdc2/ cyclin B activation at the G 2 /M transition (Qian et al, 1998a).…”
Section: Phosphorylation Of Cdc25cmentioning
confidence: 99%
“…The residues phosphorylated in cyclin B 1 have been identified in Xenopus: Ser-2, Ser-94, Ser-96, Ser-101, and Ser-113 (32,33). Mutational studies (29,32,33) have suggested that cyclin B phosphorylation is required neither for activity of the Cdc2 kinase, for Cdc2 binding, nor for cyclin B destruction in anaphase.…”
mentioning
confidence: 99%
“…The residues phosphorylated in cyclin B 1 have been identified in Xenopus: Ser-2, Ser-94, 33). Mutational studies (29,32,33) have suggested that cyclin B phosphorylation is required neither for activity of the Cdc2 kinase, for Cdc2 binding, nor for cyclin B destruction in anaphase. More recently, Li et al (34) showed that if the residues were mutated to nonphosphorylatable residues, the Cdc2-cyclin B complex does not migrate from the cytoplasm to the nucleus and therefore loses its MPF activity.…”
mentioning
confidence: 99%